2023
DOI: 10.1021/acscatal.2c06394
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Control in Palladium-Catalyzed CH2Br2 Hydrodebromination on Carbon-Based Materials by Nuclearity and Support Engineering

Abstract: Practical implementation of CH2Br2 hydrodebromination to CH3Br, an important step in the bromine-mediated functionalization of methane, is currently hindered by the lack of selective and stable catalysts, which typically deactivate over a few hours on stream. Despite ranking as the most active metal for this reaction, palladium has received limited attention due to the tendency of metal nanoparticles to form C2+ products and methane, alongside CH3Br. Herein, we explore metal nuclearity and host effects in nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A number of breakthrough works have been carried out to highlight the processes in dynamic catalysis. The dynamic behavior of gold particles in catalytic reactions has been studied by Hutchings and co-workers. The behavior of platinum, palladium, iridium particles was studied by Corma and co-workers. Growth, leaching and redeposition of/from palladium nanoparticles in cross-coupling reactions was investigated by Köhler and co-workers. ,, The dynamic behavior of palladium and the formation of [PhPdI 2 ] − and [PdI 3 ] − complexes, as well as palladium nanoparticles from soluble complexes, were studied by Reetz, de Vries and co-workers. Pérez-Ramírez and co-workers were actively investigating catalytic processes using computational methods and ML. Gai, Boyes and co-workers have contributed to the study of specific sites of the catalyst by ETEM methods. A study of the behavior of a specific Pd/NHC (NHC – N-heterocyclic carbene) catalyst molecule in cross-coupling reactions was conducted by Guo and co-workers. In a series of studies, Weckhuysen and co-workers have shown the relationship between the structure and activity of heterogeneous catalysts in industrially significant catalytic transformations, including for individual catalyst particles. The fundamental results of these and other research groups have firmly established the fact that the catalytically active particles in the reaction system should be investigated at a new combined experimental and ML level. Currently, it is clearly evident that, for a deeper study of catalytic processes, it is necessary to trace the life path of individual catalytic centers and particles.…”
Section: Analysis Of the Dynamic Behavior And Variability Of Catalyti...mentioning
confidence: 99%
“…A number of breakthrough works have been carried out to highlight the processes in dynamic catalysis. The dynamic behavior of gold particles in catalytic reactions has been studied by Hutchings and co-workers. The behavior of platinum, palladium, iridium particles was studied by Corma and co-workers. Growth, leaching and redeposition of/from palladium nanoparticles in cross-coupling reactions was investigated by Köhler and co-workers. ,, The dynamic behavior of palladium and the formation of [PhPdI 2 ] − and [PdI 3 ] − complexes, as well as palladium nanoparticles from soluble complexes, were studied by Reetz, de Vries and co-workers. Pérez-Ramírez and co-workers were actively investigating catalytic processes using computational methods and ML. Gai, Boyes and co-workers have contributed to the study of specific sites of the catalyst by ETEM methods. A study of the behavior of a specific Pd/NHC (NHC – N-heterocyclic carbene) catalyst molecule in cross-coupling reactions was conducted by Guo and co-workers. In a series of studies, Weckhuysen and co-workers have shown the relationship between the structure and activity of heterogeneous catalysts in industrially significant catalytic transformations, including for individual catalyst particles. The fundamental results of these and other research groups have firmly established the fact that the catalytically active particles in the reaction system should be investigated at a new combined experimental and ML level. Currently, it is clearly evident that, for a deeper study of catalytic processes, it is necessary to trace the life path of individual catalytic centers and particles.…”
Section: Analysis Of the Dynamic Behavior And Variability Of Catalyti...mentioning
confidence: 99%